Active pore sizes during the CO2 gasification of carbon anode at 960 °C. (15th August 2016) - Chevarin, F.; Azari, K.; Lemieux, L.; Ziegler, D.; Fafard, M.; Alamdari, H.
Highlights: Apparent reaction rates of nine particle sizes of carbon anode under CO2 at 960 °C. Measurements of the pore volume on a large pore size distribution (0.00004–100 μm). Determination of internal and external contributions during CO2 gasification. Establishment of the critical pore size parameter to reveal the limit of active pore sizes. Abstract: The objective of the present work is to distinguish and quantify the role of porosity and external surface of particles in gasification of carbon anodes and to determine a critical pore size. For this purpose nine particle size ranges with an average diameter varying from 33 to 4380 μm were reacted with CO2 at 960 °C and the pore size distribution of the samples were determined. Pore volume classification was performed using argon adsorption and mercury intrusion after being gasified. The results revealed that the open pores having a pore size of 40 μm and larger would be the most active pores for CO2 gasification of anode. It was shown that the external surface of particles and the open pores greater than the critical size are the major parameters determining the anode mass loss through its CO2 reaction.